2014
DOI: 10.9734/bjmcs/2014/9563
|View full text |Cite
|
Sign up to set email alerts
|

A Casson Fluid Model for the Steady Flow through a Stenosed Blood Vessel

Abstract: Laminar flow of blood considering the blood as a Casson fluid has been studied. It is observed that the axial velocity, volumetric flow rate and pressure gradient increase with the increase in slip velocity and decrease with growth in yield stress. The results derived have been presented both analytically and graphically for a better understanding by choosing the appropriate parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Furthermore, the results showed that with an increase in the Hartmann number, and a decrease in the flow rate. The non-Newtonian Casson blood model in the stenosed artery was investigated [14] with slip condition and concluded that slip velocity increases, whereas shear stress and yield stress reduce in a radial direction. Bioheat transfer in biological tissue and analysis of blood temperature along the artery and vein was taken into account [15].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the results showed that with an increase in the Hartmann number, and a decrease in the flow rate. The non-Newtonian Casson blood model in the stenosed artery was investigated [14] with slip condition and concluded that slip velocity increases, whereas shear stress and yield stress reduce in a radial direction. Bioheat transfer in biological tissue and analysis of blood temperature along the artery and vein was taken into account [15].…”
Section: Introductionmentioning
confidence: 99%